Challenges on the road toward a multilateral investment court - Gabrielle Kaufmann-Kohler; Michele Potestà (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2017)
Growing criticism over investor-state arbitration has led to demands for reform from various countries, international organizations and civil society groups. This Perspective addresses one option, the creation of a multilateral investment court, and reviews the main challenges that the establishment of such a court would have to master to succeed.
Keywords: 330